Iron-doped calcium phytate nanoparticles as a bio-responsive contrast agent in 1H/31P magnetic resonance imaging - Ziółkowska, Natalia; Vít, Martin; Laga, Richard; Jirák, Daniel (Scientific reports, 2022)
We present the MR properties of a novel bio-responsive phosphorus probe doped with iron for dual proton and phosphorus magnetic resonance imaging (1H/31P-MRI), which provide simultaneously complementary information. The probes consist of non-toxic biodegradable calcium phytate (CaIP6) nanoparticles doped with different amounts of cleavable paramagnetic Fe3+ ions. Phosphorus atoms in the phytate structure delivered an efficient 31P-MR signal, with iron ions altering MR contrast for both 1H and 31P-MR. The coordinated paramagnetic Fe3+ ions broadened the 31P-MR signal spectral line due to the short T2 relaxation time, resulting in more hypointense signal. However, when Fe3+ was decomplexed from the probe, relaxation times were prolonged. As a result of iron release, intensity of 1H-MR, as well as the 31P-MR signal increase. These 1H and 31P-MR dual signals triggered by iron decomplexation may have been attributable to biochemical changes in the environment with strong iron chelators, such as bacterial siderophore (deferoxamine). Analysing MR signal alternations as a proof-of-principle on a phantom at a 4.7 T magnetic field, we found that iron presence influenced 1H and 31P signals and signal recovery via iron chelation using deferoxamine.